Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Pencapaian Kinerja Guru Pendidikan Agama Katolik di Semarang - Antonius Oggi; Hartutik; Wuriningsih; Anselmus Joko Prayitno (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to explore the relationship between work motivation and discipline on the performance achievement of Catholic Religious Education (PAK) teachers in the Semarang region. The research uses a quantitative survey approach, collecting data from 15 PAK teachers through a validated questionnaire. The instruments used to measure work motivation are based on Maslow’s hierarchy of needs for the motivational aspect, while discipline is measured using indicators developed by Rivai, and performance achievement is evaluated based on parameters defined by Robbins. The findings show that motivational drive contributes 50.5% to performance achievement (R² = 0.505, p = 0.003). This indicates that work motivation has a significant impact on performance, although its contribution is lower compared to discipline. In contrast, discipline contributes more significantly to performance achievement, accounting for 66.2% (R² = 0.662, p = 0.000). This suggests that discipline is a more dominant factor in improving the performance of Catholic Religious Education teachers, as discipline is critical in achieving optimal performance. Simultaneous analysis reveals that the combination of motivation and discipline explains 72.6% of the variation in performance achievement (R² = 0.726, F = 13.893, p = 0.000). This result indicates that both variables are significantly related to performance achievement when considered together. However, partial tests show that only discipline has a significant independent impact on teacher performance, with p = 0.121, while motivation does not have a significant effect when considered separately. This study concludes that discipline functions as the main mediator in the relationship between work motivation and performance achievement. Therefore, it is essential to strengthen discipline in efforts to improve teacher performance, particularly in the context of Catholic Religious Education.